The Psychometric Properties of the Norwegian version of Multidimensional Anxiety Scale for Children – Parent version (MASC-P) - Rasmussen, Lene-Mari Potulski; Ingul, Jo Magne (PsykTestBarn, 2020)
Description: Multidimensional Anxiety Scale for Children – parent version (MASC-P) assesses anxiety symptoms in children and adolescents based on parent reports and was developed in 1997 by John March and colleagues. Arnulf Kolstad translated the instrument into Norwegian. Multi-Health Systems (MHS) is the publisher and copyright holder of the instrument. MASC-P includes 39 items, divided into four subscales. The rating scale provides a total score, indicating the extent of anxiousness, in addition to an indication of which dimension(s) of anxiety the child scores the highest. It takes approximately 10 to 15 minutes to complete the rating scale, and knowledge regarding testing, administration, scoring, and interpretation (equivalent to level B from the British Psychological Society; BPS) is recommended. Literature Search: Six Norwegian studies were included based on the literature search. The included studies reported psychometric data from parent-reports for both clinical and subclinical children aged 7-13 years. Psychometrics: Psychometric data regarding internal consistency calculations and construct validity was included. Construct validity was evaluated by comparison of scores on the MASC-P in clinical and non-clinical samples; in addition, a study looking at the ability of MASC-P scores to predict anxiety diagnosis was used to evaluate validity. Means, median, sub-group, and clinical samples, as well as concordance between children and parents, was also reported in the included studies. Conclusion: MASC-P shows adequate psychometric qualities equivalent to findings from international research. The studies show that each scale has good to excellent internal consistency, and the instrument shows an ability to differentiate between groups supporting the construct validity. However, Norwegian norm studies are lacking. Sensitivity for change has, so far, not been sufficiently examined.